Synthesizable VHDL Design for FPGAs - Bezerra, Eduardo Augusto; Lettnin, Djones Vinicius; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book provides a gradual description of very-high-speed integrated circuits hardware description language (VHDL), targeting the design of digital systems to be implemented in field-programmable gate array (FPGA) platforms. It is organized in a very didactic way. The adopted methodolgy was matured over 20 years of teaching experience in the subject. The examples in the book were planned targeting two FPGA platforms, one used widely around the world and the other one developed by a Brazilian company.
Digital Systems, FPGAs and the Design Flow -- HDL Based Designs -- Hierarchical Design -- Multiplexer and Demultiplexer -- Code Converters -- Sequential Circuits, Latches and Flip-Flops -- Synthesis of Finite State Machines -- Finite State Machines as Control Modules -- Processes in Details -- Arithmetic Circuits -- VHDL Design Examples for FPGA Synthesis.
Keywords: Electronic circuits; Electronics; Microelectronics; Software engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Software Engineering/Programming and Operating Systems